A Compromised Inheritance: Monastic Discourse and the Politics of Property Exchange in Early Twelfth-Century Flanders - Vanderputten, Steven (The journal of ecclesiastical history, 2010)
This paper explores the possibilities of assessing the social discourse of monastic groups in early twelfth-century Flanders. Through the examination of a dispute over property given by a dying noblewoman to the priory of Hesdin, it argues that both the way in which the monks and their benefactors dealt with the politics of property transfers and the discourse of the written account of these events may be interpreted, on the one hand as deliberate attempts to force a monastic understanding of property and relations with the laity upon the rural communities around Hesdin. On the other, they may be seen as the reflection of a struggle for power and status involving members of several levels of the lay elite.